User-Generated Content (UGC) and Its Impact on Tourism Marketing: A Systematic Literature Review - Sujatmiko, S; Ar, Dhita Pratiwi; Hamdat, Aminuddin; Salam, Karta Negara (Golden Ratio of Mapping Idea and Literature Format, 2025)
This study aims to systematically examine the impact of user-generated content (UGC) on tourism marketing by synthesizing empirical evidence from scholarly publications over the last decade. Grounded in a descriptive quantitative approach, the research employs a systematic literature review methodology to identify, evaluate, and integrate findings from 30 peer-reviewed journal articles published between 2010 and 2025. The review categorizes the influence of UGC across four core dimensions: destination image formation, tourist decision-making processes, emotional engagement, and strategic marketing implications. The results indicate that UGC significantly shapes both the cognitive and affective components of destination image, influences tourists’ behavioral intentions through emotional resonance, and acts as a trusted informational and social source during the travel planning cycle. Furthermore, UGC enhances marketing effectiveness when integrated responsibly into official campaigns, yet raises ethical concerns related to consent, representation, and content authenticity. The study also identifies critical gaps in current literature, including limited inclusivity in UGC representation and the risks associated with algorithmically amplified or manipulated content. The findings underscore the necessity for tourism marketers and destination management organizations to not only leverage UGC as a strategic asset but also to adopt ethical and inclusive frameworks for its governance. Ultimately, this study contributes to a more comprehensive understanding of UGC as both a communicative phenomenon and a transformative tool in the evolving landscape of digital tourism marketing.